Perioperative Outcomes, Transfusion Requirements, and Inflammatory Response After Coronary Artery Bypass Grafting With Off-Pump, Mini-Extracorporeal, and On-Pump Circulation Techniques. Issue 8 (1st December 2015) - Brinkman, William T.; Squiers, John J.; Filardo, Giovanni; Arsalan, Mani; Smith, Robert L.; Moore, David; Mack, Michael J.; DiMaio, J. Michael
Abstract : Objectives: Mini-extracorporeal circulation (MECC) units were developed to reduce postoperative morbidity, transfusion requirements, and inflammation associated with conventional on-pump coronary artery bypass (ONCAB) surgery without the technical demands of the off-pump (OPCAB) technique. We compared perioperative outcomes and inflammatory mediation among OPCAB, MECC, and ONCAB techniques. Methods: We prospectively enrolled 102 patients undergoing elective isolated coronary bypass grafting. Perfusion methods were OPCAB (n = 34), MECC (n = 34), and ONCAB (n = 34). Serial blood samples were collected to measure serum inflammatory markers. Results: There were no operative deaths or strokes. Total red blood cell (RBC) products used in OPCAB, MECC, and ONCAB patients were 0.676, 1.000, and 1.235 units, respectively. Adjusted (by splined Society of Thoracic Surgeons operative risk score) analysis showed no statistically significant differences in mean RBC product use among the different operative systems (OPCAB vs MECC, P = 0.580; OPCAB vs ONCAB, P = 0.311; MECC vs ONCAB, P = 0.633). Adjusted (by Society of Thoracic Surgeons risk score and baseline level) mean plasma level differences (24 hours postoperative - baseline) of C-reactive protein for OPCAB (117.89; 95% confidence interval [95% CI], 106.23–129.54) and for MECC (124.88; 95% CI, 113.45–136.32) were significantly higher than for ONCAB (98.82; 95% CI, 86.40–111.24). No significant adjusted differences ( P = 0.304) in interleukin-6 level changes were observed. Conclusions: Off-pump coronary artery bypass and MECC did not significantly reduce mean total RBC transfusion requirements. Off-pump coronary artery bypass and MECC were associated with greater C-reactive protein elevation than ONCAB, suggestive of an increased inflammatory response to each of these techniques.